Use of Intravital Dyes in the Assessment of Deep Burns - R. C. Sinha; J. D. P. Sinha (Indian Journal of Plastic Surgery)
1. Twenty cases of burns of varying extent were studied in which early excision of areas of deep burn with skin grafting was practised. The deep burn was outlined by Disulphine blue.